ZIP4 is required for normal progression of synapsis and for over 95% of crossovers in wheat meiosis - Draeger, Tracie N.; Rey, María-Dolores; Hayta, Sadiye; Smedley, Mark; Alabdullah, Abdul Kader; Moore, Graham; Martín, Azahara C. (Frontiers in Plant Science, 2023)
Tetraploid and hexaploid wheat have multiple genomes, with successful meiosis and preservation of fertility relying on synapsis and crossover only taking place between homologous chromosomes. In hexaploid wheat, the major meiotic gene TaZIP4-B2 (Ph1) on chromosome 5B, promotes crossover between homologous chromosomes, whilst suppressing crossover between homeologous (related) chromosomes. Tetraploid wheat has three ZIP4 copies: TtZIP4-A1 on chromosome 3A, TtZIP4-B1 on 3B and TtZIP4-B2 on 5B. Previous studies showed that ZIP4 mutations eliminate approximately 85% of crossovers, consistent with loss of the class I crossover pathway. Here, we show that disruption of two ZIP4 gene copies in Ttzip4-A1B1 double mutants, results in a 76-78% reduction in crossovers when compared to wild-type plants. Moreover, when all three copies are disrupted in Ttzip4-A1B1B2 triple mutants, crossover is reduced by over 95%, suggesting that the TtZIP4-B2 copy is also affecting class II crossovers. This implies that, in wheat, the class I and class II crossover pathways may be interlinked. When ZIP4 duplicated and diverged from chromosome 3B on wheat polyploidization, the new 5B copy, TaZIP4-B2, may have acquired an additional function to stabilize both crossover pathways. In plants deficient in all three ZIP4 copies, synapsis is delayed and does not complete, consistent with our previous studies in hexaploid wheat, when a similar delay in synapsis was observed in a 59.3Mb deletion mutant, ph1b, encompassing the TaZIP4-B2 gene on chromosome 5B. These findings confirm the requirement of ZIP4-B2 for efficient synapsis, and suggest that TtZIP4 genes have a stronger effect on synapsis than previously described in Arabidopsis and rice. Thus, ZIP4-B2 accounts for the two major phenotypes reported for Ph1, promotion of homologous synapsis and suppression of homeologous crossover.